Binding and transport of thiamine by Lactobacillus casei. - Henderson, G B (1978)
The relationship between thiamine transport and a membrane-associated thiamine-binding activity has been investigated in Lactobacillus casei. Thiamine transport proceeds via a system whose general properties are typical of active uptake processes; entry of the vitamin into the cells requires energy, is temperature dependent, exhibits saturation kinetics, and is inhibited by substrate analogs. A considerable concentration gradient of unchanged thiamine can be achieved by the system, although the vitamin is slowly metabolized to thiamine pyrophosphate. Consistent with these results, L. casei also contains a high-affinity, thiamine-binding component which could be measured by incubation of intact cells with labeled substrate at 4 degrees C (conditions under which transport is negligible). Binding was insensitive to iodoacetate, occurred at a level (0.5 nmol per 10(10) cells) nearly 20-fold higher than could be accounted for by facilitated diffusion, and was found to reside in a component of the cell membrane. Participation of this binder in thiamine transport is supported by the observations that the processes of binding and transport showed similarities in their (i) regulation by the concentration of thiamine in the growth medium, (ii) binding affinities for thiamine, and (iii) susceptibility to inhibition by thiamine analogs.